Analytical Philosophy of Technology - Rapp, F. author. aut Link
XIV, 202 p.
Keywords: Friedrich Rapp, in this magisterial and critical essay on technology, the complex human phenomenon that demands philosophy of science, philosophy of culture, moral insight, and historical sensi tivity for its understanding, writes modestly of the grave and ten tative situation in the philosophy of technology. Despite the pro found thinkers who have devoted time and imagination and ratio nal penetration, despite the massive literature now available, the varied and comparative viewpoints of political, analytic, despite metaphysical, cultural, even esthetic commitments, indeed despite the honest joining of historical and systematic methods of inves tigation, we are far from a satisfactory understanding of the joys and sorrows, the achievements and disappointments, of the tech nological saga of human societies. Professor Rapp has prepared this report on the philosophical understanding of technology for a troubled world; if ever philosophy were needed, it is in the prac tical attempt to find alternatives among technologies, to foresee dangers and opportunities, to choose with a sense of the possibil ity of fulfilling humane values. Emerson spoke of the scholar not as a specialist apart, but as 'Man thinking' and Rapp's essay so speaks to all of us, industrial world or third world, engineers or humanists, tired or energetic, fearful or optimistic.